Behavioural and socio-emotional issues among primary school students and their association with academic performance: a descriptive cross-sectional study using strength and difficulties questionnaire - S., Pragadeeshwer; Gupta, Jyoti; Singh, Yadu Vir; Chatterjee, Kunal; Nimonkar, Ravi; S., Vijayakumar (International Journal Of Community Medicine And Public Health, 2025)
Background: Behavioural and socio-emotional challenges are vital in shaping students’ academic performance and overall development. Understanding these issues early can guide targeted interventions, helping students succeed academically and emotionally. This study investigated the prevalence and impact of these challenges among primary school students. Methods: To estimate the prevalence of emotional problems, conduct problems, hyperactivity-inattention, peer problems and pro-social behaviour among primary school students. To assess the association of the above factors with their academic performance. To assess the gender differences in mental health status among primary school students. Using the teachers- strength and difficulties questionnaire (T-SDQ), a descriptive cross-sectional study was carried out on 450 primary school students. Data on socio-demographics, domain-specific impairments, and academic performance were obtained. The objectives were evaluated through prevalence rates, correlation analysis, and independent samples t-tests. The relationship between SDQ parameters and academic performance was analysed. Results: As per SDQ questionnaire Total score, 48% of the students reported with slightly raised difficulties, and 27.33% had very high difficulties. A statistically significant negative correlation (r=−0.29, p<0.001) was found between the total difficulties score and academic performance. Gender analysis revealed higher total difficulties scores in males than females (t=6.59, p<0.001). Conclusions: The study highlighted the prevalence of socio-emotional and behavioural difficulties among primary school students and how these challenges negatively influence their academic outcomes. The results emphasize the SDQ as a valuable tool for assessing students at risk and aiding the development of targeted educational and psychological support interventions.